Model Estimasi Batas Aman Gedung Shelter terhadap Tsunami di Kota Padang Menggunakan Model Inundasi Hills dan Mader - Andi Susanto; Alya Nabila; Desti Afirda; Nabilla Yusda; Nurul Annisa Dwinanda (Mataram University, 2026)
Padang City is one of the regions with a high risk of earthquakes and tsunamis. Following an earthquake that has the potential to generate a tsunami, residents must immediately evacuate to safer locations. Based on the evacuation simulations conducted by the government, the West Sumatra Grand Mosque has been designated as one of the vertical evacuation shelters. Although the building was designed to withstand earthquakes, it is also necessary to ensure that its elevation is sufficient to protect the community from tsunami hazards. Therefore, this study aims to estimate the safe tsunami limit for the second floor of the West Sumatra Grand Mosque using the Hills and Mader inundation model combined with the SCHEMA model. The results of the study provide a safe tsunami threshold interval by classifying shelter conditions into three categories: safe, when the inundation depth remains below the evacuation floor elevation; alert, when the inundation depth approaches the evacuation floor elevation, requiring evacuation to a higher floor; and unsafe, when the inundation depth exceeds the available evacuation floor elevation. These threshold intervals provide a basis for evaluating the suitability of vertical evacuation shelters under various tsunami scenarios in Padang City. The findings of this study are expected to serve as a reference for the planning and evaluation of vertical evacuation shelters and to support tsunami disaster mitigation efforts in Padang City.